Implementasi Sistem Monitoring Polusi Udara Berdasarkan Indeks Standar Pencemaran Udara Dengan Pemodelan Finite State Machine - Renal Prahardis; Dahnial Syauqy; Sabriansyah Rizqika Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Pollution is a problem that until now still can not be solved. This problem is caused by the number of users of motor vehicles that cause pollution. From these problems need a system that can determine the air quality that can immediately alert the user through the smartphone application when the condition of the air is not healthy. It is expected that with this research, people will be more concerned about their health. This system uses the Finite State Machine method (FSM) which aims to apply the working principle of the system using 3 things, namely State, Event, Action. Based on testing that has been done correlation value of sensor readings MQ2 with output voltage 94.45%, MQ7 sensor of 94.98, MQ136 sensor of 95.79. Then for the sensor DHT22 has an average error of 2.68%. In addition, the communication distance NRF can communicate at a maximum distance of 50 meters, and distance connectivity with WiFi ESP with a maximum distance of 160 meters. For data reception time, the fastest time is 1.13 seconds. Then the system in applying the Finite State Machine modeling has been successful both in the application of the Main Device and Hub Device with a percentage of success of 100%